Association of glycated albumin to hemoglobin A1c ratio with all-cause and cardiovascular mortality among US adults: A population-based cohort study. (November 2022) - Wang, Sibo; Gu, Lingfeng; Zhu, Jun; Shan, Tiankai; Sun, Jiateng; Jiang, Qiqi; Wang, Hao; Zhao, Di; Wang, Qiming; Wang, Liansheng
Abstract: Aims: To investigate the association of glycated albumin to hemoglobin A1c (GA/HbA1c) ratio, an indicator of blood glucose fluctuations, with all-cause and cardiovascular mortality among US adults. Methods: This cohort study used data from the National Health and Nutrition Examination Survey 1999–2004. Participants were linked to National Death Index mortality data through December 31, 2015. Cox proportional hazards model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs), and restricted cubic spline (RCS) regression was conducted. Results: A total of 11, 508 US adults (weighted mean age, 43.9 years; 5748 males [weighted, 48.9 %]) were included. During a median follow‑up of 13.6 years, 1963 total deaths occurred, including 383 cardiovascular deaths. After multivariable adjustments, a higher GA/HbA1c ratio was associated with a higher risk of all-cause (tertiles: P for trend < 0.001; continuous: HR 1.49 [95 % CI 1.32–1.69]) and cardiovascular (tertiles: P for trend = 0.048; continuous: HR 1.65 [95 % CI 1.27–2.14]) mortality. RCS revealed a linear relationship of GA/HbA1c ratio to mortality. Conclusions: In the nationally representative cohort of US adults, GA/HbA1c ratio was significantly associated with the risk of all-cause and cardiovascular mortality. These findings suggest that GA/HbA1c ratio may serve as an effective indicator for identifying high-risk individuals.